ZAKAT MANAGEMENT AND EFFECTIVENESS: A BIBLIOMETRIC REVIEW (2011–2025) - Baizura, Nora; Ahmad, Afida; Dawam, Siti Rafidah Muhamat; Ahmad, Jasmin Illyani; Talib, Noor Hasnita Abdul; Ali, Noor Rasidah; Mat Din, Mazura (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study presents a bibliometric analysis of research on zakat management and its effectiveness from 2011 to 2025, using the Scopus database. The purpose is to identify prevailing research methods, influential authors, journals, countries, and emerging thematic trends. The study adopts a science mapping approach, utilizing VOSviewer and Microsoft Excel to analyze 149 publications, including journal articles, conference papers, book chapters, and reviews. Data were categorized based on publication trends, subject areas, keyword co-occurrence, geographical contributions, authorship patterns, and institutional influence. The analysis reveals a steady increase in publications over the past decade, with a significant surge from 2019 onwards. Social sciences, arts and humanities, and business and management emerged as dominant subject areas, while Indonesia and Malaysia demonstrated notable research productivity. Despite the strong zakat traditions in Gulf countries, their comparatively lower research output indicates significant untapped potential for cross-country comparative studies, offering opportunities to deepen understanding and strengthen global zakat management practices. Keywords such as “zakat,” “zakat management,” and “blockchain” indicate a growing interest in integrating technology into zakat systems. The most productive institutions include Universiti Sains Islam Malaysia, Universiti Teknologi MARA, and Universitas Airlangga, highlighting strong academic engagement in Southeast Asia. Citation analysis identified key articles shaping the discourse, particularly those addressing governance, efficiency, and technology adoption. The study concludes that methodological diversity is still limited, with a need for greater adoption of mixed-method approaches and advanced analytical frameworks. These findings provide valuable insights for policymakers, practitioners, and scholars, offering a roadmap for future research to enhance the effectiveness, transparency, and socio-economic impact of zakat management.